Social support and quality of life in Chinese heart transplant recipients: mediation through uncertainty in illness and moderation by psychological resilience - Gao, Chan; Gui, Song; Zhu, Lijun; Bian, Xiaoqian; Shen, Heyong; Jiao, Can (Frontiers in Psychiatry, 2025)
IntroductionIn China’s collectivist healthcare context, the mechanisms linking social support to quality of life (QoL) in heart transplant recipients remain unclear. This study integrates Mishel’s uncertainty in illness theory and Confucian resilience frameworks to cross-sectionally examine dual pathways: direct enhancement of QoL through social support and indirect reduction of uncertainty in illness, moderated by culturally embedded psychological resilience.MethodsA nationwide cross-sectional study included 428 Chinese heart transplant recipients. Social support (SSRS), uncertainty in illness (MUIS-A), resilience (CD-RISC), and QoL (SF-36) were assessed. Mediation (PROCESS Model 4) and moderated mediation (Model 14) were tested using 5,000 bootstrap resamples, controlling for age, gender, and transplant duration.ResultsSocial support directly improved QoL (B = 0.625, p < 0.001, direct effect = 0.435, 95% CI [0.285, 0.584]) and indirectly reduced uncertainty in illness (indirect effect = 0.19, 95% CI [0.126, 0.265]). Psychological resilience moderated the uncertainty in illness-QoL link (B = 0.007, p < 0.001), with stronger negative effects in low-resilience individuals (B = -0.372 vs. high-resilience B = -0.111).ConclusionBased on this cross-sectional study, social support demonstrates significant associations with dual pathways: directly associated with improved QoL through relational support networks and indirectly linked to reduced uncertainty in illness via culturally mediated cognitive reframing. Culturally interventions integrating family-centered care and resilience training are recommended to improve long-term outcomes.